Badland beach: The Australian beach as a site of cultural remembering. (1st March 2016) - Ellison, Elizabeth
The image of the Australian beach as a place of beautiful waves and sand is popular on postcards and seen frequently in tourism campaigns around the world. And yet, the beach is a surprisingly complex spatial location. Despite its beauty, the beach can have a disturbing underbelly of crime and danger. The ongoing tension between its role as a cultural icon of myth as well as an ordinary, lived location makes it a layered landscape. This article uses the framework of Ross Gibson's 'badland' as a way of interrogating cultural memory in a lived, familiar space. By examining a combination of popular and literary texts such as fiction by Robert Drewe and the reality television show Bondi Rescue (2006–), as well as real life events, this article examines how the Australian beach can be a site of complex memory, and how this memory bleeds through and problematizes contemporary understandings and representations of the space.